2007
DOI: 10.2353/ajpath.2007.070003
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Regulates Myocardial Infarct Repair

Abstract: Myocardial infarction results in the loss of irreplaceable contractile elements. Necrotic tissue is removed by macrophages and replaced with granulation tissue, which is eventually transformed into a collagenous scar. During this process the infarcted wall thins, the left ventricular (LV) chamber dilates, and there is interstitial fibrosis and cardiomyocyte hypertrophy in the noninfarcted region of the ventricle. These changes are associated with cardiac dysfunction and progression to heart failure. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(60 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…However, FGF-2 induces cardioprotection, 44 has a role as a chemotactic factor for stem cell homing after myocardial injury, 45 induces angiogenesis, 46,47 and improves remodeling after myocardial infarction in the rat. [48][49][50] The significance of the ticagrelorinduced attenuation and clopidogrel-induced normalization of the increase in FGF-2 levels 4 weeks after infarction is unclear. Although ticagrelor attenuated adverse remodeling after infarction, clopidogrel had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, FGF-2 induces cardioprotection, 44 has a role as a chemotactic factor for stem cell homing after myocardial injury, 45 induces angiogenesis, 46,47 and improves remodeling after myocardial infarction in the rat. [48][49][50] The significance of the ticagrelorinduced attenuation and clopidogrel-induced normalization of the increase in FGF-2 levels 4 weeks after infarction is unclear. Although ticagrelor attenuated adverse remodeling after infarction, clopidogrel had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Fast Green/Picrosirius Red stains collagen red and counterstains other tissue components green to allow visualization of interstitial collagen. 20 Microscopic images were acquired with a digital camera (Leica DFC 480) on an upright microscope (Leica DMLB2).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it has been shown that compared to wild-type mice, FGF2 deficient mice develop less fibrosis when challenged by coronary ligation (88). Furthermore in response to AngII, cardiac fibroblasts release FGF2 that in an autocrine manner induces fibroblast activation and in a paracrine manner causes hypertrophic growth of cardiac myocytes (70).…”
Section: The Effects Of Paracrine Fibroblast Growth Factors On the Heartmentioning
confidence: 99%